sTREM-1 and TNF-α levels are associated with the clinical outcome of leprosy patients - Bezerra-Santos, Márcio; Bomfim, Lays G. Santos; Santos, Camilla N. Oliveira; Cunha, Maria Wiliane N.; de Moraes, Eduardo J. Rocha; Cazzaniga, Rodrigo A.; Tenório, Martha D. L.; Araujo, Jonnia M. Sherlock; Menezes-Silva, Lucas; Magalhães, Lucas Sousa; Barreto, Aline S.; Reed, Steven G.; et al. (Frontiers in Medicine, 2023)
Leprosy reaction (LR) and physical disability (PD) are the most significant clinical complications of leprosy. Herein, we assessed the circulating serum-sTREM-1 and TNF-α levels and their genetic polymorphisms in leprosy. Serum-sTREM-1 and TNF-α levels were measured in leprosy patients (LP) before treatment (n = 51) and from their household contacts (HHCs; n = 25). DNA samples were genotyped using TREM-1 rs2234246 and TNF-α rs1800629-SNP in 210 LPs and 168 endemic controls. The circulating sTREM-1 and TNF-α levels are higher in the multibacillary form. The ROC curve of the serum-sTREM-1 levels was able to differentiate LR from non-LR and PD from non-PD. Similarly, LPs with serum-sTREM-1 levels >210 pg/ml have 3-fold and 6-fold higher chances of presenting with LR and PD, respectively. Genotypes CC+CT of the TREM-1 were associated with leprosy. Taken together, our analyses indicated that sTREM-1 and TNF-α play an important role in the pathogenesis of leprosy and provide promising biomarkers to assist in the diagnosis of leprosy complications.